The effect of self-efficacy and mathematical anxiety on students' mathematical communication skills - Ari Septian; Sarah Inayah; Ismi Nur Afifah (RANGE: Jurnal Pendidikan Matematika, 2024)
This study aims to identify and examine the effect of self-efficacy and mathematical anxiety on students' mathematical communication skills. This study used a quantitative method with a survey design. The population of this study was students of class X at SMA Negeri 2 Cianjur and the sample used was students of class X-D to X-G, totaling 34 people. The sampling technique was carried out by purposive sampling. Data regarding self-efficacy and mathematical anxiety using a questionnaire each amounted to 20 statements and data regarding students' mathematical communication abilities used a test which amounted to 5 description questions with quadratic function material. The data processing technique used is multiple linear regression tests, by fulfilling the prerequisite tests including the normality test, homoscedasticity test, linearity test and multicollinearity test. Based on the research results, it was found that the P value was 0.074, meaning > 0.05, then H0 was accepted and H1 was rejected. This means that there is no influence between self-efficacy and mathematical anxiety on students' mathematical abilities.